ChemInform Abstract: Photovoltaics with Ferroelectrics: Current Status and Beyond. Issue 34 (4th August 2016) - Paillard, Charles; Bai, Xiaofei; Infante, Ingrid C.; Guennou, Mael; Geneste, Gregory; Alexe, Marin; Kreisel, Jens; Dkhil, Brahim
Abstract: Review: 114 refs.